An invitation to quantum econometrics - Hung T. Nguyen (2018)
© 2018, Springer International Publishing AG. We elaborate on the possibility to considering quantum probability calculus to improve statistical methods in economics in general, and in quantitative finance, in particular. A tutorial on the analogy between quantum mechanics and models in econometrics, using Kolmogorov probability theory, is given. Several research issues are mentioned.